2021
DOI: 10.1021/acs.jpcc.1c07723
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Pseudoelasticity in Gold Nanocrystals

Abstract: Pseudoelasticity in metal nanocrystals allows for shape recovery from strains much larger than their bulk counterparts. This fascinating property could be used to engineer self-healing or reconfigurable materials, but to take full advantage of its possibilities, a deeper understanding of its mechanism and limitations is needed. For instance, it is unknown whether room-temperature pseudoelasticity can occur in all metal nanocrystals without the introduction of plastic damage. Here we report the use of nonhydros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Even worse, the changes in the LSPR due to different effects can be quite similar to each other. Pressure-induced LSPR shifts of AuNS have been mainly associated with changes of the surrounding refractive index and the Au electron concentration in highly compressed NP as well as to reshaping into oblate deformations, particularly under nonhydrostatic pressure conditions. , However, these effects are more intricate in AuNR due to their axial symmetry, making them more susceptible to deformation under nonhydrostatic compression, and to their greater tendency to form aggregates. The lack of reversibility of the AuNR extinction spectra in upstroke and downstroke supports this view. , Consequently, an adequate interpretation of such structural changes through plasmonics requires confirmation by other complementary techniques, for the model to be validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even worse, the changes in the LSPR due to different effects can be quite similar to each other. Pressure-induced LSPR shifts of AuNS have been mainly associated with changes of the surrounding refractive index and the Au electron concentration in highly compressed NP as well as to reshaping into oblate deformations, particularly under nonhydrostatic pressure conditions. , However, these effects are more intricate in AuNR due to their axial symmetry, making them more susceptible to deformation under nonhydrostatic compression, and to their greater tendency to form aggregates. The lack of reversibility of the AuNR extinction spectra in upstroke and downstroke supports this view. , Consequently, an adequate interpretation of such structural changes through plasmonics requires confirmation by other complementary techniques, for the model to be validated.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-induced LSPR shifts of AuNS have been mainly associated with changes of the surrounding refractive index 1 3 and the Au electron concentration in highly compressed NP 10 12 as well as to reshaping into oblate deformations, particularly under nonhydrostatic pressure conditions. 13 , 14 However, these effects are more intricate in AuNR due to their axial symmetry, making them more susceptible to deformation under nonhydrostatic compression, and to their greater tendency to form aggregates. The lack of reversibility of the AuNR extinction spectra in upstroke and downstroke supports this view.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure is an important variable to consider in the study of the fundamental properties of nanoparticles and the role of size and increased surface area in determining the said properties. Size dependence in high-pressure phase diagrams has been observed in metallic and semiconductor nanocrystals, and similar studies have reported intriguing pressure-dependent optical and mechanical properties of nanocrystals and their assemblies.…”
Section: Introductionmentioning
confidence: 78%
“…Determination of mechanical properties, such as Young’s and bulk moduli, has consistently been the subject of intense research for NPs, especially metallic and semiconducting NPs . Among various approaches reported, the most commonly applied is the compressibility measured by high-pressure XRD. Degrees of compression of the unit cell volumes can be derived from pressure-induced shifts of XRD diffraction peaks, which can then be used to calculate bulk moduli of the NP materials by employing the Birch–Murnaghan equation of state (EOS). To date, literature reports comparing the mechanical properties of bulk and nanomaterials have been inconsistent.…”
Section: Pressure-induced Property Changes In Inorganic Npsmentioning
confidence: 99%